Penerapan SOP Pelayanan Untuk Pemberian Bantuan Satu Keluarga Satu Kolam Kabupaten Jember - Aprilia Uzlifatul Jannah; Rini Puji Astuti; Amalia Mujahadah; Lailatul Maghfiroh (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The problem of stunting in Jember Regency is a serious concern for the Government because it is number two in East Java Province. Therefore, through the Jember Regency Fisheries Service, it is trying to reduce the stunting rate by utilizing the one family, one pond program. Based on the procurement information system (syrup) of the Jember Fisheries Service, the program costs Rp. 1.062 billion which comes from the 2023 Regional Revenue and Expenditure Budget (APDB). According to data obtained from 2022 data, there are 35 families who received assistance from the one family, one pond program. Every year the number of families receiving assistance from the one family, one pool program increases, until by 2023 there will be 150 families receiving assistance from the program.